Motivation of Teacher Leaders to Use Canva in Designing Learning Media Based on the UTAUT 2 Model in Elementary Schools - puji isratulhasanah; Sofwan, Muhammad; Hayati, Suci (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This research aims to describe the motivation of mobilizing teachers in using the Canva application to design learning media, examined based on the UTAUT 2 model. This review process encompasses six aspects including Performance expectancy, Effort expectancy, social influence, facilitating conditions, hedonic motivation, and price value. This research was conducted using a qualitative phenomenological approach at Al-Falah Islamic Elementary School in Jambi during the even semester of the 2024/2025 Academic Year. The research subjects were mobilizing teachers at Al-Falah Islamic Elementary School in Jambi. Data was collected through interviews and documentation study analysis, with validity and reliability tested using source triangulation. The research results show that the application of the UTAUT 2 model can provide a deep understanding of factors influencing the motivation of mobilizing teachers in using the Canva application to design learning media in Elementary Schools. The adoption of the UTAUT 2 model in understanding the motivation of mobilizing teachers using the Canva application in designing learning media shows that mobilizing teachers experience ease and benefits from the Canva application, thus encouraging them to integrate it in designing learning media. The Canva application makes a significant contribution to the learning process through the creation of quality visual and engaging learning media that increases students' learning motivation and understanding of teaching materials. This indicates the role of the Canva application as a tool in designing learning media in elementary schools and as a motivational trigger for mobilizing teachers. The effectiveness of the Canva application supports the creation of a more dynamic and interactive learning environment, which aligns with the demands of modern education. From the research results, it can be concluded that the UTAUT 2 model collectively encourages the motivation of mobilizing teachers in the adoption and continued use of the Canva application for designing learning media.